Sleep disturbances in youth at‐risk for serious mental illness. Issue 3 (13th November 2019) - Stowkowy, Jacqueline; Brummitt, Kali; Bonneville, Dominique; Goldstein, Benjamin I.; Wang, JianLi; Kennedy, Sidney H.; Bray, Signe; Lebel, Catherine; MacQueen, Glenda; Addington, Jean
Abstract: Aim: To investigate sleep behaviours of youth at‐risk for serious mental illness (SMI). Methods: This study included 243 youth, ages 12 to 25:42 healthy controls, 41 asymptomatic youth at‐risk for mental illness (stage 0); 53 help‐seeking youth experiencing distress (stage 1a) and 107 youth with attenuated syndromes (stage 1b). The Pittsburgh Sleep Quality Index was used to assess sleep dysfunction. Results: Stage 1b individuals indicated the greatest deficit in global sleep dysfunction ( F = 26.18, P < .0001). Stages 1a and 1b reported significantly worse subjective sleep quality, a longer sleep latency, increased use of sleep medications as well as greater daytime dysfunction compared to the asymptomatic groups. Conclusion: Research investigating sleep behaviours of youth considered to be at‐risk for SMI is limited. This study provides early evidence that sleep disturbances are worse for individuals considered to be at higher risk of illness development.